Determinasi Kualitas Pengelolaan Keuangan Di Sekretariat DPRD NTB - Nurazlinda; Rusli Amrul; Baiq Kisnawati; M. Wahyullah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This study aims to analyze the factors that influence the quality of financial reports in the secretariat of the Regional People's Representative Council (DPRD) of West Nusa Tenggara (NTB) Province. The independent variables in this study are the Regional Financial Accounting System, Human Resource Competence, Control and Utilization of Technology while the dependent variable is the Quality of Financial Reports. The study was conducted at the NTB Provincial DPRD Secretariat Office with a sample of 50 financial staff who understand and carry out the financial transaction process. Data were obtained by distributing 50 questionnaires to respondents then the results of the questionnaire were processed using SPSS 29. The data were analyzed using data quality tests (validity and reliability), classical assumption tests (normality, multicollinearity and heteroscedasticity), multiple linear regression analysis, hypothesis tests (partial) and determination coefficient tests. The results of this study indicate that the Regional Financial Accounting System and Utilization of Information Technology have a significant positive effect on the variable of Financial Report Quality in the NTB Provincial DPRD Secretariat. Human Resource Competence and Internal Control do not have a significant effect on the Quality of Financial Reports of the Secretariat in the NTB Provincial DPRD